Towards Exascale Computing Architecture and Its Prototype: Services and Infrastructure - Meizner, Jan; Nowakowski, Piotr; Kapala, Jan; Wojtowicz, Patryk; Bubak, Marian; Tran, Viet; Bobák, Martin; Höb, Maximilian (Computing and Informatics, 2021)
This paper presents the design and implementation of a scalable compute platform for processing large data sets in the scope of the EU H2020 project PROCESS. We are presenting requirements of the platform, related works, infrastructure with focus on the compute components and finally results of our work.